Dosing challenges and benefits of vericiguat in a patient with decompensated heart failure: a case report - Speranza Sánchez, Mario (2023)
Vericiguat has emerged as a promising add-on therapy for decompensated heart failure with reduced ejection fraction (HFrEF) patients requiring hospitalization or IV diuretic administration. In the VICTORIA trial (Vericiguat Global Study in Subjects with Heart Failure with Reduced Ejection Fraction), vericiguat was demonstrated to significantly reduce mortality and hospitalization rates. However, the effect of vericiguat on patients receiving SGLT2 inhibitors remains uncertain. In this report, we present a complicated case of dilated heart failure receiving low doses of foundational therapy due to a patient's intolerance but still experiencing recurrent hospital readmissions. Following six months of low-dose vericiguat as an add-on therapy, the patient exhibited important improvements in various clinical parameters, including cardiac and renal function. Nonetheless, further investigation is crucial to substantiate the additional benefits of combination therapy. These findings provide further evidence for the potential benefits of vericiguat when treating HFrEF.